Pathophysiology and Clinical Manifestations of Hypogonadism - Nurma'rifatullah; Ni Made Meta Satya Buda Duarsa; Ranti Filarma Negara Purnama; Yumna Iftinan Khalda; Eva Triani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Hypogonadism is a condition where the function of the gonad glands decreases, resulting in a decrease in hormone levels due to the hypothalamus-pituitary-gonad (HPG) axis. Hypogonadism occurs in approximately 2.1% – 12.8% of the middle-aged to older male population. This article was written to find out more about explaining the pathophysiology and clinical symptoms of hypogonadism. The method used is literature reflection combined with related search sources from the National Center for Biotechnology Information (NCBI), Google Scholar, and Research Gate. The results of a literature review of articles carried out can conclude that hypogonadism often causes symptoms of delayed puberty, loss of libido, erectile dysfunction, loss of muscle mass, and depression. Hypogonadism is also classified based on the reason into primary and secondary hypogonadism. Primary hypogonadism occurs due to gonadal dysfunction, while secondary hypogonadism occurs due to dysfunction of the hypothalamus and/or pituitary gland.